Primary and Recurrent Repair of Incisional Hernia Based on Biomechanical Considerations to Avoid Mesh-Related Complications - Nessel, Regine; Löffler, Thorsten; Rinn, Johannes; Lösel, Philipp; Voss, Samuel; Heuveline, Vincent; Vollmer, Matthias; Görich, Johannes; Ludwig, Yannique-Maximilian; Al-Hileh, Luai; Kallinowski, Friedrich (Frontiers in Surgery, 2021)
Aim Mechanical principles successfully guide the construction of polymer material composites in engineering. Since the abdominal wall is a polymer composite augmented with a textile during incisional hernia repair we ask: can incisional hernia be repaired safely and durably based on biomechanical principles? Material and methods Repair materials were assessed on a self-built bench test using pulse loads to elude influences on the reconstruction of the abdominal wall. Tissue elasticity was analyzed preoperatively as needed with computed tomography at rest and during Valsalva’s maneuver. Preoperatively, the critical retention force of the reconstruction to pulse loads was calculated and a biomechanically durable repair was designed based on the needs of the individual patient. Intraoperatively, the design was adjusted as needed. Hernia meshes with high grip factors (Progrip®, Dahlhausen® Cicat) were used for the repairs. Mesh sizes, fixation elements and reconstructive details were oriented on the biomechanical design. All patients recieved single-shot antibiosis. Patients were discharged after full ambulation was achieved. Results A total of 163 patients (82 males and 81 females) were treated for incisional hernia in four hospitals by ten surgeons. Primary hernia was repaired in 119 patients. Recurrent hernia was operated on in 44 cases. Recurrent hernia was significantly larger (median 161 cm² versus 78 cm²; u-test: p = 0.00714). Re-do surgery took significantly longer (median 229 min versus 150 min; p < 0.00001) since recurrent disease required more often transversus abdominis release (70 % versus 47 %). GRIP tended to be higher in recurrent repair (p = 0.01828). Complication rates (15 %) and hospital stay were the same (6 versus 6 days; p = 0.28462). After one year, no recurrence was detected in either group. Pain levels were equally low in both primary and recurrent hernia repairs (median NAS = 0 in both groups at rest and under load, p = 0.88866). Conclusion Incisional hernia can safely and durably be repaired based on biomechanical principles both in primary and recurrent disease. The GRIP concept provides a base for the application of biomechanical principles in incisional hernia repair.